SirT1 gain-of-function increases energy efficiency and prevents diabetes in mice - Banks, Alexander S. (2008)
In yeast, worms and flies, an extra copy of the gene encoding the Sirtuin Sir2 increases metabolic efficiency, as does administration of polyphenols like resveratrol, thought to act through Sirtuins. But evidence that Sirtuin gain-of-function results in increased metabolic efficiency in mammals is limited. We generated transgenic mice with moderate overexpression of SirT1, designed to mimic the Sirtuin gain-of-function that improves metabolism in C.elegans. These mice exhibit normal insulin sensitivity, but decreased food intake and locomotor activity, resulting in decreased energy expenditure. However, in various models of insulin resistance and diabetes, SirT1 transgenics display improved glucose tolerance due to decreased hepatic glucose production and increased adiponectin levels, without changes in body weight or composition. We conclude that SirT1 gain-of-function primes the organism for metabolic adaptation to insulin resistance, increasing hepatic insulin sensitivity and decreasing whole-body energy requirements. These findings have important implications for Sirtuin-based therapies in humans.